The Sense of Existence - Alexandre Billon (Ergo, An Open Access Journal of Philosophy)
If I see, hear, or touch a sparrow, the sparrow seems real to me. Unlike Bigfoot or Santa Claus, it seems to exist; I will therefore judge that it does indeed exist. The “sense of existence” refers to the kind of awareness that typically grounds such ordinary judgments of existence or “reality.” The sense of existence has been invoked by Humeans, Kantians, Ideologists, and the phenomenological tradition to make substantial philosophical claims. However, it is extremely controversial; its very existence has been called into question. This paper aims to clarify the nature and reality of the sense of existence by studying a psychiatric condition in which the sense appears to be disrupted: depersonalization disorder (DPD).